THE PRACTICE OF EDUCATION TOURISM: A CASE OF BERUGA’ ALAM INSTITUTE - Marham Jupri Hadi; Tris Shakti Permata; Tarmizi Tarmizi (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
Education tourism refers to a travel program to a location with the primary goal is to engage in learning activities directly associated with a tourist destination. The current study explores the practice of edutourism as implemented by Beruga’ Alam Institute which involved college students of English language education. This case study employed participant observations, in-depth interviews, and documentation to gain a deep understanding regarding the case under study. 13 participants consisting of 7 students of English language education, a program coordinator, 2 tour guides and the head of the institute took part in the interviews. Collected data were analyzed interactively to conclude the study. The findings of this study revealed that the concept of educational tourism practiced in Beruga’ Alam Institute reflected its five fundamental vision namely: a) well behaved; b) being insightful; c) being skillful; d) being self-reliant and; e) contribution. The promoted model of edutourism in Beruga’ Alam begins with meditation, followed by exploration, reflection and ended with a publication. These stages feature every edutour program. The edutour programs offered to college students include nature exploration, art and culture exploration, Kings and Saints (graveyards) visits, charity and social life exploration, staying with the locals, local figures visits and other programs. Students were also offered short courses like photography writing, cooking class, and public speaking during the tours. Finally, based on the participants’ reflection on their edutour experiences, all of them express positive views on the programs and were willing to participate in the future education tourism programs.